Population Demographics of Helopeltis bradyi Waterhouse (Hemiptera: Miridae) from Three Different Locations - Izzati, Dian Nurul; Witjaksono, Witjaksono; Harjaka, Tri (Jurnal Perlindungan Tanaman Indonesia, 2023)
Helopeltis bradyi Waterhouse has been reported to attack tea plantations in Batang District and cocoa plantations in Sleman District and Kulon Progo District. Information about the life parameters of H. bradyi reared using alternative feed cucumbers in the laboratory helps pest management efforts. This study aimed to determine the life demography of H. bradyi from two plants and three different locations. The study was conducted with cohort observations consisting of gross reproduction rate (GRR), net reproduction rate (Ro), intrinsic growth (r), average generation length (T), and population doubling time (DT) of three populations of H. bradyi. Results showed that there were differences in living individuals (ax), mortality, and life duration of the three H. bradyi populations. The survival type of the three populations of H. bradyi was classified as type IV. The survival of the three H. bradyi populations were influenced by their ability to adapt to new environments. From the three populations of H. bradyi observed, Sleman population survived longer because they had adapted to the rearing environment and were able to maintain the population numbers for two generations. Demographic parameters of H.bradyi from Sleman showed gross reproduction rate (GRR) of 88 individuals/generation, net reproduction rate (Ro) of .97 individuals/parents/generation, the increase in population rate (r) of 0.02 individuals/species/day, extended duration (T) of 39.50 days, and doubling time (DT) of 40.49 days.